Rheology of rock salt for salt tectonics modeling - Shi-Yuan Li (KeAi Communications Co., Ltd., 2016)
Abstract Numerical modeling of salt tectonics is a rapidly evolving field; however, the constitutive equations to model long-term rock salt rheology in nature still remain controversial. Firstly, we built a database about the strain rate versus the differential stress through collecting the data from salt creep experiments at a range of temperatures (20–200 °C) in laboratories. The aim is to collect data about salt deformation in nature, and the flow properties can be extracted from the data in laboratory experiments. Moreover, as an important preparation for salt tectonics modeling, a numerical model based on creep experiments of rock salt was developed in order to verify the specific model using the Abaqus package. Finally, under the condition of low differential stresses, the deformation mechanism would be extrapolated and discussed according to microstructure research. Since the studies of salt deformation in nature are the reliable extrapolation of laboratory data, we simplified the rock salt rheology to dislocation creep corresponding to power law creep (n = 5) with the appropriate material parameters in the salt tectonic modeling.